Design and Fabrication of Long-Term Stable Dye-Sensitized Solar Cells: Effect of Water Contents in Electrolytes on the Performance - Park, Jongwoo; Lee, Phillip; Ko, Min Jae (KOREAN SOC PRECISION ENG, 2019)
The effects of water-containing I-/I-3(-) liquid electrolytes on the photovoltaic performance and long-term stability of ruthenium based complex Z907 dye was examined in dye-sensitized solar cells (DSSCs). Despite of high water content up to 60 vol% in organic solvent-based liquid electrolyte, the photovoltaic properties and long-term stability measured under the standard global (G) air-mass (AM) 1.5 solar irradiation were not significantly affected. The underlying correlation between the effects of water and the photovoltaic performances were identified by UV-visible spectroscopy and electrochemical impedance spectroscopy. We investigated the long-term stability of performance for DSSCs in conjunction with I-/I-3(-) redox electrolytes in different water compositions. The findings revealed that the competitive photovoltaic performance and long-term stability of water-containing DSSCs mainly depends on the hydrophobicity of dye as well as the transport phenomena of I-3(-) throughout the electrolytes. The water-based DSSCs proposed herein are free from water permeation issues and these results will provide great insight into the development of less expensive and more environmental friendly DSSCs.
Keywords: THIN-FILM; TIO2; EFFICIENCY